Ethical or practical: An empirical study of students' choices in simulated business scenarios - White, Charles S. (Journal of business ethics, 1993)
Graduate and undergraduate students were asked to evaluate the ethicality and practicality of the lead character in several case scenarios. Students' responses indicated they believed practicality was more important than ethicality. The majority of students were able to determine the correct ethicality of the cases presented to them. The authors conclude that more research is needed in the antecedents of a student's value system.